A Comparative Study of the Effect of Brain Dominance on Learners' Performance in Multiple Choice of English Grammar - Laily Komaril Syafrilia (Graduate Program, University of Islam Malang, 2019)
Language testing was placed in the last part of teaching and learning activity in all school. It is as tool to measure students' competence to be their performance to show their capability. In other side, beside technique and method to improve and enlarge students' performance were founded, the factors in which become the reason of both decreasing and increasing competence and performance are studied. One of them is students' preference because of their personalities. This research tries to dig pupils' performance because of their differences in term of brain dominance. Grammar test is used as the ruler since it has components in language skill namely reading and listening which are use mostly in language testing such as TOEFL and IELTS.